Ethical Issues in Online Psychotherapy: A Narrative Review - Stoll, Julia; Müller, Jonas Adrian; Trachsel, Manuel (Frontiers in Psychiatry, 2020)
Background: The provision of psychotherapy over distance using technology is a growing market reaching many patients and therefore the risks and benefits need to be known by all psychotherapists whether they themselves practice online or not. This comprehensive review of the main ethical arguments for and against different forms of online psychotherapy aims to enhance discussion of ethical issues in this growing area. Methods: A search of three databases (PubMed, PsycINFO, Web of Science) was conducted in August 2019 using a specific search protocol yielding 249 publications. Results: Of 24 ethical arguments in favor of online psychotherapy and 32 against, the top five ethical arguments in favor of online psychotherapy were (1) increased access to psychotherapy and service availability and flexibility; (2) therapy benefits and enhanced communication; (3) advantages related to specific client characteristics (e.g., remote location); (4) convenience, satisfaction, acceptance and increased demand; and (5) economic advantages. The top five ethical arguments against engagement in online psychotherapy were (1) privacy, confidentiality and security issues; (2) therapist competence and need for special training; (3) communication issues specific to technology; (4) research gaps; and (5) emergency issues. Conclusions: The findings may be of help to practitioners in deciding whether to engage in online psychotherapy, and in informing patients about risks and benefits, improving ethical guidelines, and stimulating further ethical discussion. The findings are argumentative and qualitative in nature, and further quantitative research is needed.